2019
DOI: 10.3389/fpsyt.2019.00451
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Public Mental Health: A Focused Review

Abstract: Psychological trauma has developed into a very common concept in the scientific community, in mental health care, as well as in popular language and mass media. The purpose of this article is to show the relevance of the discipline of traumatic stress studies to the field of public mental health by examining central concepts and findings concerning trauma and its aftermath and examining implications for public mental health. Attention is paid to the diagnosis of posttraumatic stress disorder (PTSD) and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 36 publications
0
61
0
1
Order By: Relevance
“…Those studies that reported on change in reactions over time all concluded that there was a reduction in impact over time. This would be expected given what is known about the processes of grief and of recovery following trauma (Kleber, 2019; Zisook & Shear, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Those studies that reported on change in reactions over time all concluded that there was a reduction in impact over time. This would be expected given what is known about the processes of grief and of recovery following trauma (Kleber, 2019; Zisook & Shear, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The role of exposure to traumatic events such as 9/11 and their prolonged impact on physical and mental health outcomes is the subject of increasing focus by investigators [28,29,30,31]. The literature on potential mechanisms underlying associations between stress, psychological distress and hearing problems in humans is extremely limited [32,33,34]; there is also a need for more research in animal models examining the role of acute physical and psychological trauma and chronic stress on potential adverse effects on the cochlea and auditory cortex in order to identify mechanisms potentially amendable to intervention [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on trauma and post-trauma has changed how both clinicians and the lay public think about life-threatening events and their impact (32,44). With the passage of time and the expanding literature base, clinical practitioners and the general public are better informed as to the incidence, prevalence, and pernicious deleterious effects of exposure to traumatic events (45,46). Similarly, awareness of the various intervention programs and their reported efficacy has increased as well (6,47,48).…”
Section: Traumatic Bereavementsmentioning
confidence: 99%